THE INFLUENCE OF RETURN ON ASSETS, DEBT TO ASSETS RATIO AND CURRENT RATIO ON FINANCIAL DISTRESS - Rosi, Nandias Alfiana; Hasanuh, Nanu - (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aimed to find out the influence of Return On Assets, Debt to Assets Ratioand Current Ratiopartially and simultaneously on Financial Distress. The data collection was conducted from annual report from five cosmetic and household companies listed in Indonesia Stock Exchange in 2013 – 2018. The data were analyzed through hypotheses test and classical assumption test using multiple  linear regression.  The result of partially test in this research, it indicated  that Return On Assets and Debt to Assets Ratio has influence on financial distress while the Current Ratio do not have influence on Financial Distress. The simultaneously result, Return On Assets, Debt to Assets Ratio and Current Ratio have influence on Financial Distress.   Keywords : Financial Distress; Return on Assets; Debt to Assets Ratio; Current Ratio.